Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Derive the transformation on a position vector p (x,y,z) that results in its reflection across the plane?
whose equation is n . ( r - r0) = 0, where r0 is a point on the plane and n is a normal vector to the plane. (n is not necessarily a unit vector).
Then use the transformation you derived to find the transformed equation of the line
L: r = (1, 1, 1) + t (-1, 0, 1)
After reflecting across the plane 2x - y + 3z = 1.
As another application, find the transformed equation of the plane 5x + y + z = 7 across the plane
2x - y + 3z = 1.
2 Answers
- IndicaLv 77 years agoFavorite Answer
Assume that n is unit and at end replace n by n/|n|
If perp from P to plane is PN then NP = ((r−r₀)•n)n = (nᵀ(r−r₀))n = n(nᵀ(r−r₀)) = (nnᵀ)(r−r₀)
∴ If reflected point is r’ then r’ = r + 2*PN = r – 2(nnᵀ)(r—r₀)
Replace n by n/|n| to get r’−r₀ = R(r−r₀) where reflection matrix R = I − 2(nᵀn)/|n|²
Note that R is its own inverse so r’−r₀ = R(r−r₀) and r−r₀ = R(r’−r₀)
These can be written as r = a+Rr’ or r’ = a+Rr where a = r₀−Rr₀
For 2x−y+3z=1 n=(2,−1,3), |n|²=14 and choose r₀=(0,−1,0)
nnᵀ = { {4,−2,6}, {−2,1,−3}, {6,−3,9} } so R =(1/14){ {6,4,−12}, {4,12,6}, {−12,6,−4} }
a = (0,−1,0) − R(0,−1,0) = (1/7)(2,−1,3)
For L : (1,1,1) → (1/7)(1,10−2) : (−1,0,1) → (−1,0,1)
So transformation of L is r = (1/7)(1,10,−2) + t(−1,0,1)
The plane mᵀr=p → mᵀ(a+Rr’) = p ≡ (mᵀR)r’ = p−mᵀa
With m=(5,1,1) & p=7 this gives mᵀR = (1/7)(11,19,−29) and p−mᵀa = 7−12/7 = 37/7
Equation of reflected plane is 11x+19y−29z = 37
- ?Lv 77 years ago
Well,
the question is interesting, but i have to work... so maybe more this evening (french time !)
so what i can offer is :
n can be transformed in a unit vector (let' s admit this)
u is the unit vector according to (r-r0) : so (obviously) : r-r0 = ((r-r0) . u)u
then, let be: v = u x n (vector product) and w = n x v = n x (u x n)
then we have the decomposition:
r-r0 = ((r-r0).n)n + ((r-r0).w)w
and therefore, if S is the symmetry according to plane P passing through r0
S(r-r0) = - ((r-r0).n)n + ((r-r0).w)w
hope it' ll help !!